A GLIMPSE OF ACADEMIC AND MEDIA DISCOURSES OF AGRITOURISM IN SANTA ROSA DE LIMA-SC (STATE OF SANTA CATARINA, BRAZIL) - Yolanda Flores e Silva; Felipe Borborema Cunha Lima; Luana de Sousa Oliveira (Revista Brasileira de Pesquisa em Turismo, 2011)
This paper presents a discussion of tourism in rural areas, as an activity that transforms and changes people and environments, as it is primarily a field that permeates the lives and contexts over different dimensions of human living. We analyze this situation from the intersections and differences between the discourses produced in two surveys conducted in the last two years. Each one, from a distinct look (Research 1 - academic discourse / research 2 - media discourses) about the same phenomenon presents different evaluation axes about the perceptions that individuals can build in the same situation. For the preparation of this text we draw the following methodological paths: reading the results of each survey, selection of speeches given the categories of convergent and divergent analysis, and finally the joint analysis of data and discussion of them. At the end we realize the existence in the two speeches, a format or a distorted image tourism phenomenon in question and therefore able to raise expectations or discourage unnecessary and even harmful to the proposed future growth of tourism in the region.